Crystallization and preliminary crystallographic studies of the NAD(+)-dependent deacetylase HST1 from Saccharomyces cerevisiae - Zhu, Yuwei (International Union of Crystallography, 2011)

(untitled)
The Saccharomyces cerevisiae NAD(+)-dependent deacetylase HST1 belongs to the class III HDAC family; it acts as a transcriptional corepressor for the specific middle sporulation and de novo NAD(+)-biosynthesis genes and also takes part in the SET3C and SUM1–RFM1–HST1 complexes. Structural information on HST1 and its related complexes would be helpful in order to understand the structural basis of its deacetylation mechanism and the assembly of these complexes. Here, HST1(156–503) was expressed and crystallized. Crystals grown by the hanging-drop vapour-diffusion method diffracted to 2.90 Å resolution and belonged to space group P2(1), with unit-cell parameters a = 40.2, b = 101.7, c = 43.9 Å, β = 103.9°. Both Matthews coefficient analysis and the self-rotation function suggested the presence of four molecules per asymmetric unit in the crystal, with a solvent content of 49.76% (V (M) = 2.45 Å(3) Da(−1)).